Implementation of the Lean User Experience Method in Home Care Registration Information System Application Yakes Telkom Regional West Java - Sofalina, Fresa Dwi Juniar; Rusdiana, Yudi (IJISTECH (International Journal of Information System and Technology), 2023)
The Lean method is used to determine the UI UX of a website-based Home Care service registration application. This method can help writers to make applications that are effective and in accordance with the psychological and geographic conditions of the user. Based on the results of the design using the lean method, the appearance of the Home Care service registration application is designed as simple as possible and does not make it difficult for users to operate it. This reason is due to the age of application users who incidentally are officers in the range of 30 years to 55 years.